ANALISIS KADAR ASAM ASETAT (CH3COOH) PADA BUAH PISANG AMBON YANG DIFERMENTASI SELAMA 7, 10, 14, DAN 21 HARI - Triana, Linda; Ratnawati, Gervacia Jenny; Kurniati, Iis; Sari, Emilda (poltekkes kemenkes pontianak, 2022)
Banana trees are plants that come from the humid tropics and include herbaceous plants from Southeast Asia, including Indonesian. Several types of bananas are scattered in various parts of Indonesia, namely Ambon bananas, Ambon moss bananas, Barangan bananas, Emas bananas, Kepok bananas, Lampung bananas, jackfruit bananas, horn bananas, and Raja Bulu bananas.One of the food ingredients that can be processed into processed products that have commercial value is bananas. Processing of bananas consists of two processing groups, that is: processing of unripe bananas and processing of ripe (ripe) bananas. One of the processing of ripe bananas can be done by fermentation. The end products of fermentation include energy, carbon dioxide, ethanol, ammonia, lactic acid, and acetic acid. Normally, acetic acid can be consumed after ripe bananas have been fermented for at least 3 days. Making acetic acid with bananas as raw material is called banana vinegar. This study aimed to observe differences in the levels of acetic acid (CH3COOH) in Ambon bananas fermented for 7, 10, 14, and 21 days. The results of the study on average levels of acetic acid in Ambon bananas fermented for 7, 10, 14 and 21 days were 0.59%, 0.68%, 0.77% and 0.84%. And from the results of statistic (p = 0.062 at the 95% confidence level (p > 0.05)).